Development and validation of context-specific components of obstetric violence: Experiences from the central zone of Tanzania - Theresia J. Masoi; Stephen M. Kibusi; Nathanael Sirili; Lilian Teddy Mselle (PLoS ONE, 2025)
Background Despite the known consequences of obstetric violence, studies have encountered challenges in defining and fully understanding obstetric violence. This difficulty arises from a relative scarcity of research addressing the definition of obstetric violence across various cultures and contexts. As a result, there is a lack of consensus regarding the operational definitions of the components of obstetric violence and variations that may be influenced by geographical and cultural factors. Objective This study describes the process of developing and validating the context specific components of obstetric violence in the Central Zone of Tanzania. Methods An iterative mixed-methods design was used, using the following stages; 1. collecting and analysing qualitative data on context specific components of obstetric violence along with a literature review 2. assessing the content validity with 24 maternal health experts and face validity with 27 postnatal mothers and nine health care providers. Descriptive analysis was employed to analyse participants’ characteristics and Likert scale responses from experts, postnatal mothers and health care providers. Item-level Content Validity Index (I-CVI) and Item-face Validity Index (I-FVI) was computed for each component. Results Seven categories of obstetric violence components were identified through this process.These included: physical violence, lack of supportive care and treatment, subjugation care, an unfavourable care environment, sexual violence, verbal violence, emotional and psychological violence. In addition, 24 subcategories of obstetric violence were identified. The Item-Level Content Validity Index (I-CVI) ranged from 0.791 to 0.958, while the Item-Face Validity Index (I-FVI) ranged from 0.777 to 0.925. Conclusion The validated components of obstetric violence in Tanzania will contribute to a better understanding of the issue within the Tanzanian context.This in turn, may facilitate a more accurate assessment of the magnitude and impact of obstetric violence while helping to identify key areas for intervention and policy development to promote respectful maternity care.